Determinants of Inflation Volatility: The Role of Institutions, Shocks, and Economic Development - Merza, Ebrahim; Alawin, Mohammad; Husain, Muna (International Journal of Economics and Financial Issues, 2025)
Inflation volatility remains one of the most important challenges for policymakers, households, and businesses alike. When prices fluctuate unpredictably, people lose confidence in their ability to plan ahead. Households struggle to budget and save, firms hesitate to invest and hire, and policymakers face higher pressure to act without clear guidance. Recent global crises—whether energy shocks, food price surges, or supply chain disruptions—have shown how quickly instability spreads across borders. This raises a central question: why are some countries more vulnerable to inflation volatility than others? Following Aisen and Veiga (2006), this study addresses that question by examining the determinants of inflation volatility across three income-based groups: lower-middle-income, upper-middle-income, and high-income economies, using panel data covering the period 1996-2024. Using both fixed and random-effects models, we find that inflation persistence and high inflation levels are the strongest drivers of volatility, while higher income levels and stronger governance support price stability. External shocks—such as trade openness, oil price fluctuations, and exchange-rate misalignments— show varied effects across income groups, emphasizing the importance of context-specific responses. The findings suggest that when countries invest in credible institutions and reliable policies, they can transform external shocks from being destabilizing forces into manageable challenges.